2016
DOI: 10.3389/fpls.2016.00276
|View full text |Cite
|
Sign up to set email alerts
|

High Salinity Induces Different Oxidative Stress and Antioxidant Responses in Maize Seedlings Organs

Abstract: Salinity negatively affects plant growth and causes significant crop yield losses world-wide. Maize is an economically important cereal crop affected by high salinity. In this study, maize seedlings were subjected to 75 mM and 150 mM NaCl, to emulate high soil salinity. Roots, mature leaves (basal leaf-pair 1,2) and young leaves (distal leaf-pair 3,4) were harvested after 3 weeks of sowing. Roots showed the highest reduction in biomass, followed by mature and young leaves in the salt-stressed plants. Concomita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
219
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(251 citation statements)
references
References 78 publications
27
219
3
2
Order By: Relevance
“…In studies with other crops, researchers have also observed decreased shoot-root ratios with increasing salinity (Pearen et al, 1997;Bayuelo-Jiménez et al, 2003;Acosta-Motos et al, 2015). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The observation that salinity has less of an adverse effect on root growth compared with shoot growth is consistent with other observations related to stress, such as P deficiency (Fredeen et al, 1989), N deficiency (Sattelmacher et al, 1990), and drought stress (Sharp et al, 1988;Buwalda and Lenz, 1992).…”
Section: Salt Tolerancesupporting
confidence: 74%
See 1 more Smart Citation
“…In studies with other crops, researchers have also observed decreased shoot-root ratios with increasing salinity (Pearen et al, 1997;Bayuelo-Jiménez et al, 2003;Acosta-Motos et al, 2015). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The observation that salinity has less of an adverse effect on root growth compared with shoot growth is consistent with other observations related to stress, such as P deficiency (Fredeen et al, 1989), N deficiency (Sattelmacher et al, 1990), and drought stress (Sharp et al, 1988;Buwalda and Lenz, 1992).…”
Section: Salt Tolerancesupporting
confidence: 74%
“…However, shoot growth has been found to be more adversely affected by salinity than root growth (Munns and Termaat, 1986). However, there are some reports of increased shoot-root ratios (Bernstein et al, 2004;AbdElgawad et al, 2016). The root biomass per plant was reduced by 18 and 49%, respectively, while the shoot biomass was reduced by 50 and 73%, respectively.…”
Section: Salt Tolerancementioning
confidence: 97%
“…Photosynthetic activity of most plants decreases under saline conditions because PSII activity is disturbed and thylakoid membrane along with its pigments is damaged due to formation of ROS under salinity stress (Dombrowski , Naeem et al , Shaheen et al , Wu et al , Deinlein et al , AbdElgawad et al , Askary et al , Gomes et al ). Like many other stresses, the deficiency of iron can also generate ROS and disturb the electron transport chain in the chloroplast because iron plays an important role in it (Graziano and Lamattina ).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity same as water stress, leads to oxidative stress in plant cells due to increased production of reactive oxygen species (ROS) such as superoxide radicals (O2 .-), hydrogen peroxide (H2O2) and hydroxyl radical (HO . ) (Yadava et al, 2013;AbdElgawad et al, 2016;Asadi Karam and Keramat, 2017 ). ROS's are partially reduced forms of atmospheric oxygen, which are produced in vital processes such as photorespiration, photosynthesis and respiration.…”
Section: Introductionmentioning
confidence: 99%